Early enteral nutrition after head and neck surgery with free tissue transfer reconstruction. Issue 1 (February 2022) - Imai, Takayuki; Saijo, Satoshi; Fujii, Keitaro; Nakazato, Akira; Nakamura, Kazuki; Miyakura, Yuya; Yamazaki, Tomoko; Goto, Takahiro; Asada, Yukinori
Abstract: Objective: Early enteral nutrition is essential for enhancing recovery after surgery. However, to date, no detailed study has been conducted on the feasibility of early enteral nutrition in patients undergoing head and neck surgery with free tissue transfer reconstruction (HNS-FTTR) and the risk factors for difficulty with early enteral nutrition. Methods: We retrospectively analyzed 102 patients who underwent HNS-FTTR at our institution; 61 underwent free jejunal reconstruction (FJ) and 41 did not. We investigated the achievement of early enteral nutrition within 24 and 48 h after surgery and the discontinuation of enteral nutrition after its initiation within 7 days after surgery. Results: Enteral nutrition could be started in 81/102 (79.4%) and 99/102 (97.1%) patients within 24 and 48 h, respectively. Cases of difficulty with early enteral nutrition accounted for 21/102 (20.6%) patients. The multivariate analysis revealed that FJ was a significant independent risk factor for difficulty with early enteral nutrition (odds ratio: 4.054, P = 0.042). The risk factors for difficulty with early enteral nutrition in patients who underwent FJ were also investigated, and the multivariate analysis showed that blood loss of ≥158 mL was a significant independent risk factor (odds ratio: 3.505, P = 0.044). Conclusions: Early enteral nutrition seemed to be provided with no problems in patients without FJ. FJ was a significant risk factor for difficulty with early enteral nutrition. Increased intraoperative blood loss was a significant risk factor for difficulty with early enteral nutrition in patients undergoing FJ; therefore, patients' abdominal symptoms and gastric residual volume should be carefully monitored in such cases.